Description of a new species of Lethe (Lepidoptera, Nymphalidae, Satyrinae) from western Yunnan, China - Lang, Song-Yun; Duan, Shao-Zhong (Zootaxa, 2016)
A new species, Lethe tengchongensis Lang sp. nov., from Tengchong County, Mts. Gaoligong, western Yunnan Province, SW China is described and illustrated.